2007
DOI: 10.1042/bj20061653
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of short-term ERK activation by electromagnetic fields at mobile phone frequencies

Abstract: The exposure to non-thermal microwave electromagnetic fields generated by mobile phones affects the expression of many proteins. This effect on transcription and protein stability can be mediated by the MAPK (mitogen-activated protein kinase) cascades, which serve as central signalling pathways and govern essentially all stimulated cellular processes. Indeed, long-term exposure of cells to mobile phone irradiation results in the activation of p38 as well as the ERK (extracellular-signal-regulated kinase) MAPKs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
177
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(196 citation statements)
references
References 47 publications
(63 reference statements)
10
177
0
9
Order By: Relevance
“…Phosphorylation of JNK1/2 was detected at Figure 1D), while p38 activation was not detected ( Figure 1E). Recently, it was reported that ERK was activated within 5 min of the radiation, with the peak activity occurring within 10-15 min, whereas no phosphorylation of JNKs or p38 was detected within a short time of exposure [12]. Our results with human LECs are consistent with that study.…”
Section: Dear Editorsupporting
confidence: 83%
“…Phosphorylation of JNK1/2 was detected at Figure 1D), while p38 activation was not detected ( Figure 1E). Recently, it was reported that ERK was activated within 5 min of the radiation, with the peak activity occurring within 10-15 min, whereas no phosphorylation of JNKs or p38 was detected within a short time of exposure [12]. Our results with human LECs are consistent with that study.…”
Section: Dear Editorsupporting
confidence: 83%
“…However, biological agents are impeded by membranes and require special mechanisms to gain access to the cell interior. Friedman et al [23] have demonstrated that the initial step in transmitting extracellular information from the plasma membrane to the nucleus of the cell occurs when NADH oxidase rapidly generates reactive oxygen species (ROS). These ROS stimulate matrix metalloproteinases that allow them to cleave and release heparin binding epidermal growth factor.…”
Section: Emf Interaction With Signaling Pathwaysmentioning
confidence: 99%
“…A number of studies have been conducted to elucidate the mechanism by which the ELF-MF affects the production of O 2 -in the cell. For example, it has been demonstrated that an exposure of Hela cells to electromagnetic field (875 MHz) only for a few minutes increased reactive oxygen species (Friedman et al, 2007). This has been attributed to an increase in the NADH oxidase activity.…”
Section: Discussionmentioning
confidence: 99%